PET/CT imaging in polymyalgia rheumatica: praepubic (18)F-FDG uptake correlates with pectineus and adductor longus muscles enthesitis and with tenosynovitis - Rehak, Zdenek (Radiol Oncol, 2017)
BACKGROUND: The role of (18)F-fluorodeoxyglucose positron emission computed tomography ((18)F-FDG PET/CT) is increasing in the diagnosis of polymyalgia rheumatica (PMR), one of the most common inflammatory rheumatic diseases. In addition to other locations, increased (18)F-FDG accumulation has been detected in the praepubic region in some patients. However, a deeper description and pathophysiological explanation of this increased praepubic accumulation has been lacking. The aim of the presented study is to confirm a decrease in praepubic (18)F-FDG accumulation in response to therapy and to describe potential correlations to other (18)F-FDG PET/CT scan characteristics during the course of disease. As a secondary objective, we describe the pathological aspects of the observed praepubic (18)F-FDG uptake. PATIENTS AND METHODS: A retrospective review of patients with newly suspected PMR undergoing baseline and follow up (18)F-FDG PET/CT between February 2010 and March 2016 is given. Those with a visually detected presence of praepubic (18)F-FDG accumulation were further analysed. The uptake was assessed visually and also semi-quantitatively in the defined region of interest by calculation of target-to-liver ratios. Other regions typical for PMR were systematically described as well (shoulders, hips, sternoclavicular joints, ischiogluteal bursae, spinous interspaces). RESULTS: Twenty-three out of 89 screened patients (26%) presented with initial praepubic (18)F-FDG PET/CT positivity, 15 of whom also underwent follow up (18)F-FDG PET/CT examination. Five out of 15 patients presented with increased (18)F-FDG accumulation in large arteries as a sign of giant cell arteritis. During follow up examination, decrease in (18)F-FDG accumulation caused by therapeutic intervention was observed in all evaluated locations in all analysed patients and no new positivity was indicated, including periarticular, extraarticular tissues or target large vessels. Praepubical accumulation of (18)F-FDG was diminished in all patients (15/15, 100%) after treatment with steroids. CONCLUSIONS: Increased praepubic (18)F-FDG uptake in patients with PMR is relatively common and this region should be systematically evaluated during differential diagnosis of rheumatic and malignant disease. Praepubic inflammation is probably related to enthesitis and tenosynovitis at the origin of pectineus and adductor longus muscles ventrally from the pubis.